2017
DOI: 10.1089/neu.2016.4955
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Prediction after Traumatic Spinal Cord Injury Based on Acute Clinical Factors

Abstract: Spinal cord injury (SCI) is a devastating condition that affects patients on both a personal and societal level. The objective of the study is to improve the prediction of long-term functional outcome following SCI based on the acute clinical findings. A total of 76 patients with acute traumatic SCI were prospectively enrolled in a cohort study in a single Level I trauma center. Spinal Cord Independence Measure (SCIM) at 1 year after the trauma was the primary outcome. Potential predictors of functional outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 26 publications
0
39
0
2
Order By: Relevance
“…Wilson et al created a clinical prediction model for determining the long-term functional outcome based on acute clinical and imaging factors obtained within 3 days of injury; however, the coefficient of determination (R 2 ), which measures the accuracy of the model, was 0·52 [16]. Kaminski et al created a functional outcome prediction model based on acute clinical factors, and their R 2 was 0·57 [39]. Matsushita et al and Dalkilic et al reported the correlation between the MRI lesion area and the neurologic prognosis, and their R 2 calculated by the correlation coefficient was 0·28 and 0·29, respectively [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al created a clinical prediction model for determining the long-term functional outcome based on acute clinical and imaging factors obtained within 3 days of injury; however, the coefficient of determination (R 2 ), which measures the accuracy of the model, was 0·52 [16]. Kaminski et al created a functional outcome prediction model based on acute clinical factors, and their R 2 was 0·57 [39]. Matsushita et al and Dalkilic et al reported the correlation between the MRI lesion area and the neurologic prognosis, and their R 2 calculated by the correlation coefficient was 0·28 and 0·29, respectively [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several research groups have reported poor feasibility and accuracy of current methods in classifying injury severity and predicting neurologic outcomes due to the heterogeneity of SCI or limitations of each imaging technology (Krishna et al 2014 ; Hicks et al 2017 ). For example, Kaminski et al ( 2017 ) created a prediction model including four different acute clinical parameters associated with an R 2 value of 0.573. Here, we investigated the temporal changes in the expression level of 40 cytokines using cytokine arrays.…”
Section: Discussionmentioning
confidence: 99%
“… 38 However researches on human show gender-related differences in recovery after SCI have not been found. 39 , 40 The evidence of estrogen effects in SCI remains inconclusive. Therefore, the finding of our work tends to fit female rodents.…”
Section: Discussionmentioning
confidence: 99%